Regional mechanisms to ensure freedom of expression and the right to information - Yuldosheva Shoxista Tolqinovna (Zien Journals, 2024)
Freedom of expression, or freedom of speech, is essential to a democracy. It means that everyone can participate in political debates, and the media holds those in power accountable. A free, independent and diverse media plays the role of “protecting the public interest” by informing the public and holding government accountable
Keywords: Freedom of speech; mechanism; international law; document